Expansion of Oil Palm Plantations in Indonesia’s Frontier: Problems of Externalities and the Future of Local and Indigenous Communities - Andrianto, A.; Komarudin, Heru; Pacheco, P. (MDPI, 2019)
The expansion of oil palm plantations in Papua province, Indonesia, involves the conversion of forests, among other land types in the landscapes, which are a source of clan members’ livelihoods. The way in which this expansion occurs makes it necessary to understand the factors associated with why companies look for frontier lands and what externalities are generated during both the land acquisition and plantation development periods. Using a spatial analysis of the concession areas, along with data from household surveys of each clan from the Auyu, Mandobo, and Marind tribes who release land to companies, we find that investors are motivated to profit from timber harvested from the clearing of lands for plantations, activity that is facilitated by the local government. Land acquisition and plantation development have resulted in externalities to indigenous landowners in the form of time and money lost in a series of meetings and consultations involving clan members and traditional elders. Other externalities include the reduced welfare of people due to loss of livelihoods, and impacts on food security.